2004
DOI: 10.1023/b:bmmd.0000031752.63215.61
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Vapor Transport Channels for the Improved Attachment of a Medical Device to the Human Body

Abstract: Attachment of a small, medical device to the human body for an extended period of time in an ambulatory setting requires the careful consideration of the physical form of the device and the physiological constraints limiting the time a device will stay on the skin. Factors such as the size of the device, the area of the device available for attachment to the skin, and the occlusive nature of the materials in the device are likely to affect adhesion. Here, plastic acrylic disks, 25 mm in diameter, containing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…This loss of adhesion was speculated to be caused by moisture at the interface, where the presence of free water could perturb the skin-adhesive interactions or cause a change in skin surface energy through hydration [10][11][12]. Regardless of the failure mechanism, it has become widely accepted that the removal of moisture from the skin-adhesive interface is vital for retaining adhesion during perspiration [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…This loss of adhesion was speculated to be caused by moisture at the interface, where the presence of free water could perturb the skin-adhesive interactions or cause a change in skin surface energy through hydration [10][11][12]. Regardless of the failure mechanism, it has become widely accepted that the removal of moisture from the skin-adhesive interface is vital for retaining adhesion during perspiration [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Solvent-borne acrylic PSAs offer several advantages, such as excellent aging characteristics and resistance to elevated temperatures and plasticizers, exceptional optical clarity due to the polymer compatibility and non-yellowing. They also have the highest balance of adhesion and cohesion and an excellent water resistance [4].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Cunningham and Lowery showed that the transportation of moisture vapor affected the adhesion of medical device to the human skin. 2 The acrylic plastic disks with air-filled channels remained on the skin three times longer than the disks without the channels because of better water vapor transport. Additional interested property of backing layer is Young's modulus.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of backing materials have influence on drug delivery profile, adhesion of the patch to skin, wear ability and skin irritation. 1,2 The backing layer can be classified into occlusive and nonocclusive types. The backing layer that has a water vapor transmission rate (WVTR) less than 26 g/m 2 /day is considered to be occlusive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation